The Notion of Reader Orientation in Business Texts - Tam, Esther Chelliab (Journal of Modern Languages, 2017)
This study is a preliminary on the notion of ‘orientation’ (Cooper, 1982), as an interactive feature in written business texts. ‘Orientation’ involves two essential aspects of interaction. The first, is the intended ‘message’, and the second is the reaction to it, that is, its ‘reception’. The study also aims to suggest some categories for the interaction produced by the adjectives identified in the corpus. In addition, some typical features and patterns of the lexical items under scrutiny are identified to offer pedagogical insights into the teaching of writing of business texts.